ANALISIS PENGEMBANGAN KARIR PEGAWAI PADA BANK BNI CABANG KOTA TANJUNGPINANG - Muqtafin Muqtafin; Satriadi Satriadi; Risnawati Risnawati (JURNAL CAFETARIA, 2022)
The purpose of this study was to find out about Employee Career Development at the BANK BNI Tanjungpinang Branch. This type of research is qualitative research. The method in this research is descriptive with a qualitative approach, data processing is carried out through three stages which include data reduction, data presentation and drawing conclusions using data validity test analysis using triangulation. Based on the results of the study, it can be concluded that the Career Development of Employees at BNI Bank Tanjungpinang City Branch is good, career development is based on rules and procedures that have been in effect, as has been done with honest treatment where all promotion criteria are always objective but there are some places that are usually preogrative rights This is for a sensitive position, usually for certain places such as managing human resources, but usually all viewed from the last 3 years' performance so it does not necessarily mean that later in promotion the position also sees hard competent and soft competent. Based on the results of the study it was found that from the employees themselves who chose the position they wanted to occupy, the employees chose their place of work, if it was felt to be incompatible then they would not take the opportunity. many employees want to promote but don't want to go to Anambas, Natuna and Lingga, they may choose their positions but their placement.